Influence of the director's communicative leadership in the integration of primary education teachers of the educational institution 892 - 8187 “La Arboleda”, Santa Rosa District - Ancón - Malpartida Santos, Felicita (2020)
This article analyzes the communicative leadership of the principal and the integration of primary school teachers of the educational institution 892 - 8187 “La Arboleda”, Santa Rosa - Ancón district. The main objective is to determine the influence between the established variables. Methodologically, the research is of quantitative type, descriptive-correlational level and quasi-experimental cross-sectional design. The population and sample of study selected corresponds to 20 teachers, not probabilistically chosen, the Shapiro-Wilk test was used to test the normality of a set of data since it is considered one of the most powerful tests for the normality test, being the most appropriate because the sample is small. The study determined that there is a stronger influence on the communicative leadership of the principal on the integration of teachers through the empathy presented by the director towards his teachers in charge.